Torque Removal Evaluation of Screw in One-Piece and Two-Piece Abutments Tightened with a Handheld screwdriver - Jalil Ghanbarzadeh (Journal of Dental Materials and Techniques, 2013)
Introduction: Some clinicians use a handheld screw driver instead of a torque wrench to definitively tighten abutment screws. The aim of this study was to compare the removal torque of one-piece and two-piece abutments tightened with a handheld driver and a torque control ratchet. Methods: 40 ITI implants were placed in acrylic blocks and divided into 4 groups. In groups one and two, 10 ITI one-piece abutments (Solid®) and in groups three and four, 10 ITI two-piece abutments (Synocta®) were placed on the implants. In groups one and three abutments were tightened by 5 experienced males and 5 experienced females using a handheld driver. In groups two and four abutments were tightened using a torque wrench with torque values of 10, 20 and 35 N.cm. Insertion torque and removal torque values of the abutments were measured with a digital torque meter. Results: The insertion torque values (ITVs) of males in both abutments were significantly higher than those of females. ITVs in both Solid® and Synocta® abutments tightened with a handheld screwdriver were similar to the torque of 20 N.cm in the torque wrench. Removal torque values (RTVs) of solid® abutments were higher than those of synocta® abutments. Conclusion: The one- piece abutments (solid®) showed higher RTVs than the two-piece abutments (synocta®). Hand driver does not produce sufficient preload force for the final tightening of the abutment